2021
DOI: 10.3390/genes12030419
|View full text |Cite
|
Sign up to set email alerts
|

Set-Based Rare Variant Expression Quantitative Trait Loci in Blood and Brain from Alzheimer Disease Study Participants

Abstract: Because studies of rare variant effects on gene expression have limited power, we investigated set-based methods to identify rare expression quantitative trait loci (eQTL) related to Alzheimer disease (AD). Gene-level and pathway-level cis rare-eQTL mapping was performed genome-wide using gene expression data derived from blood donated by 713 Alzheimer’s Disease Neuroimaging Initiative participants and from brain tissues donated by 475 Religious Orders Study/Memory and Aging Project participants. The associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 84 publications
(86 reference statements)
0
4
0
Order By: Relevance
“…Gene‐ and pathway‐level mapping of rare eQTL in ADNI blood samples and brain tissue from the Religious Orders Study/Memory and Aging Project (ROSMAP) cohort identified rare and low‐frequency variants involved in inflammation mediated by cytokines and chemokine signaling. 191 These included five genes previously linked to AD ( ALOX5AP, CXCR2, FPR2, GRB2, IFNAR1 ). Rare variants in NLRC3 were associated with neuroinflammation (CSF YKL‐40).…”
Section: Adni's Contributions To Understanding Ad Disease Progressionmentioning
confidence: 99%
“…Gene‐ and pathway‐level mapping of rare eQTL in ADNI blood samples and brain tissue from the Religious Orders Study/Memory and Aging Project (ROSMAP) cohort identified rare and low‐frequency variants involved in inflammation mediated by cytokines and chemokine signaling. 191 These included five genes previously linked to AD ( ALOX5AP, CXCR2, FPR2, GRB2, IFNAR1 ). Rare variants in NLRC3 were associated with neuroinflammation (CSF YKL‐40).…”
Section: Adni's Contributions To Understanding Ad Disease Progressionmentioning
confidence: 99%
“…These rare‐eQTLs have been implicated in disease phenotypes as well, with Patel et al. finding many rare QTLs in genes and pathways implicated in Alzheimer's disease (Patel et al., 2021b).…”
Section: Strategic Approachmentioning
confidence: 99%
“…Ferraro et al showed that this pattern of rare-variant enrichment in extreme molecular phenotypes was limited to RNA expression alone and found in allelic expression and alternative splicing outliers (Ferraro et al, 2020). These rare-eQTLs have been implicated in disease phenotypes as well, with Patel et al finding many rare QTLs in genes and pathways implicated in Alzheimer's disease (Patel et al, 2021b).…”
Section: Rare-eqtlsmentioning
confidence: 99%
“…Specifically, plasma BACE1-AS levels are differentially expressed in the pre-symptomatic phase, indicating long non-coding RNA molecules may be a viable pre-symptomatic diagnostic target. Patel, Zhang [7] demonstrate that rare genetic variants significantly impact gene expression and gene co-expression in Alzheimer's disease, indicating that set-based gene analyses are necessary to fully capture gene dynamics related to disease progression. Those pathway-level analyses confirmed substantial immune and inflammatory expression quantitative trait loci associated with Alzheimer's disease, as suggested in the review published in this Special Issue [1].…”
mentioning
confidence: 99%